Long-run relationship of the HYV Boro rice yields in the northern region of Bangladesh - Karmokar, Provash Kumar; Shitan, Mahendran; Beg, A. B. M. Rabiul Alam (WFL Publisher, 2013)
Bangladesh is a large agrarian country and the people of Bangladesh mainly depend on rice for their food and calories intake. High Yielding Variety(HYV) Boro rice constitutes a large share in the domestic food grain of the country. HYV Boro rice is cultivated widely in the northern region (Rajshahi division) of Bangladesh. In this study, three districts were selected from the Rajshahi division to measure the long-run relationship. By using the Engle-Granger methodology, we found that multicointegration exists between the yields of HYV Boro rice of Bogra district and the estimated yield of Dinajpur district. The error correction model (ECM) shows that approximately 54.7% of any deviation from the long-run path is corrected within a year. The results of this study would be helpful for policy makers dealing with food security.